2021
DOI: 10.1186/s12935-021-01879-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of KIF20A by transcription factor IRF6 affects the progression of renal clear cell carcinoma

Abstract: Background Renal clear cell carcinoma (ccRCC) is one of the most common malignant tumors, whose incidence is increasing year by year. IRF6 plays an important role in the occurrence of tumors, although there is yet no report on its expression in ccRCC. Methods The expression of IRF6 and KIF20A in ccRCC was predicted by GEPIA and HAP databases. In addition, GEPIA database predicted the relationship between IRF6 and KIF20A expressions and the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…6C&D). Previous study indicated that IRF6 mediated renal clear cell carcinoma cell apoptosis [34]. Consistently, we found that IRF6 also mediated the renal cell apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6C&D). Previous study indicated that IRF6 mediated renal clear cell carcinoma cell apoptosis [34]. Consistently, we found that IRF6 also mediated the renal cell apoptosis (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that IRF6 mediated the Renal clear cell carcinoma cell apoptosis. [34]The prediction from the miRBase database indicated that miR-221-5p contained the complementary sequence of IRF6 (Fig. 6A).…”
Section: Irf6 Is a Direct Mir-221-5p Target Gene And Mediates I/r-ind...mentioning
confidence: 99%
“…GEPIA resource assembles TCGA and GTEx databases to focus on the expression of human genes and the correlation of the gene expression in multiple types of cancer; provides developmental information for evaluating the genes with aberrant expression in cancer. The GEPIA resource was highly cited in the previous studies [9][10][11], including ccRCC [12,13]. In the present study, we used the GEPIA resource to analyze the lncRNA that was most associated with the survival rates of patients with ccRCC and found PEBP1P2, whose expression was decreased in ccRCC and associated with the poor survival rates of ccRCC patients.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported that IRF6 mediates renal clear cell carcinoma cell apoptosis [ 34 ]. The prediction from the miRBase database indicated that miR-221-5p contained the complementary sequence of IRF6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 C and D). A previous study indicated that IRF6 mediated renal clear cell carcinoma cell apoptosis [ 34 ]. Consistently, we found that IRF6 mediated renal cell apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%